One Chance : A Memoir - Potts, Paul, 1970- (New York Weinstein Books, 2013)
A memoir by international opera star Paul Potts, winner of the first season of "Britain's Got Talent."
Include Color Illustration
Keywords: Potts, Paul, 1970- -- Singers -- Great Britain